Musico-dramatic spatial analyses of aerial action in contemporary opera performance - Gardner, K (2022)
Operatic performances invoking circus action have gained prominence since the late twentieth century. This thesis argues for the musico-dramatic contribution of aerial circus action in contemporary opera performance. There are two central claims of the thesis. One, that the spatial relationships created by the actual aerial circus actions in an opera performance contribute to musico-dramatic interpretations of an opera. Two, that the interdisciplinary study of opera and circus can offer insights into our understanding of how an opera in performance creates and communicates meaning.